The United Nations and collective security - Wilson, Gary (Law teacher); Taylor & Francis (Online service). (Milton Park, Abingdon, Oxon New York, NY Routledge, 2014)
"The role of the United Nations in collective security has been evolving since its inception in 1945. This book provides an understanding of the main tools of the UN collective security from a legal perspective, and considers the manner of their evolution. Set within a theoretical, historical and political context, the book demonstrates how the concept of collective security has been implemented within the UN system and how the practice of the organisation has evolved to meet new challenges for the maintenance of international peace and security. Although the operation of the UN collective security system has always taken place against geopolitical dynamics, which often restrict its capabilities, the story of the UN has also demonstrated the remarkable ability of its mechanisms and processes to develop and adapt effectively in both legal and political terms to take account of changing circumstances and pressures. Through specific consideration of the UN system's use of diplomatic means, sanctions, peacekeeping and military enforcement measures, the book highlights the limitations and genuine possibilities of the UN collective security system, and the role which regional organisations can play within this system. The book will be of interest to scholars of both international law and international relations"-- Provided by publisher.
The Concept of Collective Security -- The UN Charter's System of Collective Security -- A Brief Overview of Key Events of the UN Era -- Diplomatic Responses to Security Threats -- The Use of Non-Military Sanctions -- Peacekeeping -- Military Enforcement Action -- Regional Arrangements and the UN Collective Security System -- Conclusions.
Includes bibliographical references (pages 223-242) and index.
Keywords: United Nations -- Peacekeeping forces; Electronic books; Security, International; LAW / General; LAW / International; POLITICAL SCIENCE / International Relations / General